One-Step Fabrication of 2.5D CuMoOx Interdigital Microelectrodes Using Numerically Controlled Electric Discharge Machining for Coplanar Micro-Supercapacitors - Shunqi Yang; Ri Chen; Fu Huang; Wenxia Wang; Igor Zhitomirsky (Micromachines)
With the increasing market demands for wearable and portable electronic devices, binary metal oxides (BMOs) with a remarkable capacity and good structure stability have been considered as a promising candidate for fabricating coplanar micro-supercapacitors (CMSCs), serving as the power source. However, the current fabrication methods for BMO microelectrodes are complex, which greatly hinder their further development and application in BMO CMSCs. Herein, the one-step fabrication of 2.5D CuMoOx-based CMSCs (CuMoCMSCs) has been realized by numerically controlled electric discharge machining (NCEDM) for the first time. In addition, the controllable capacity of CuMoCMSCs has been achieved by adjusting the NCEDM-machining voltage. The CuMoCMSCs machined by a machining voltage of 60 V (CuMoCMSCs60) showed the best performance. The fabricated CuMoCMSCs60 with binary metal oxides could operate at an ultra-high scanning rate of 10 V s−1, and gained a capacity of 40.3 mF cm−2 (1.1 mA cm−2), which is more than 4 times higher than that of MoOx-based CMSCs (MoCMSCs60) with a single metal oxide. This is because CuMoOx BMOs materials overcome the poor electroconductivity problem of the MoOx single metal oxide. This one-step and numerically controlled fabrication technique developed in this research opens a new vision for preparing BMO materials, BMO microelectrodes, and BMO microdevices in an environmental, automatic, and intelligent way.